The Correlation Between Self-Directed Learning and Students' Academic Writing Skills Undergraduate Program of English Education - Windiana Rizkiani; Ahmad Zamzam; Arafiq (Journal of Classroom Action Research, 2023)
Success in academic writing cannot be separated from students' level of self-directed learning. Therefore, this study aims to measure the correlation between self-directed learning levels and academic writing. This study used the quantitative method and inferential analysis in Pearson Products Moment SPSS 25 version to identify and clarify the hypothesis and the correlation between self-directed learning level and academic writing. The participants of this study were 25 students 9th semester who had taken the proposal exam at the English Language Education University of Mataram. To collect the data, the researcher used distributed SRSSDL questionnaire and a test. The finding of this study indicates that most students experienced a high level of self-directed learning and academic writing in percentage 32.00 %, followed by 68.00% of moderate one. The correlation between the two variables is statistically significant at the .01 level. Pearson's coefficient value is .801, which shows a very strong correlation between the level of self-directed learning and academic writing. Therefore, the Null Hypothesis (Ho) is rejected and the Alternative Hypothesis (Ha) is accepted because the significance value is 2 ≥ (more than) a. It means that there is a significant correlation between two variables, that is, self-directed learning level and academic writing